O contencioso do algodão: cenários para mudança na política de subsídios dos EUA - Lima, Thiago [UNESP] (Centro de Estudos Globais da Universidade de Brasília, 2006)
The article examines the non compliance of the United States with the WTO report on the cotton dispute. It is argued that that attitude is not rational from the unitary and rational State point of view, but it can be explained through a fragmented perspective of the State. Thus, although the administration desired to comply, cotton growers and congressists, strengthened by political institutions, constrained the needed changes. In the end, scenarios about possible changes in the U.S. agriculture subsidy policy are projected.

Neste artigo se examina a não adequação dos EUA ao parecer da OMC no contencioso do algodão. Argumenta-se que tal atitude é irracional do ponto de vista do Estado unitário e racional, mas que pode ser explicada por meio de uma perspectiva fragmentada do Estado. Assim, embora a administração desejasse a adequação, cotonicultores e congressistas potencializados por instituições políticas constrangeram as mudanças necessárias. Ao final são projetados cenários para a modificação da política de subsídios agrícolas dos EUA.
The cotton dispute: scenarios for change in the U.S. subsidies policy
Keywords: U.S. trade policy; cotton; WTO; Política comercial americana; algodão; OMC